Post – operative analgesia in patients under thoracotomy - Giavasopoulos, Evangelos (Health & Research Journal, 2019)
The thoracotomy is one of the most painful surgery operations, and the final outcome is directly associated with the postoperative pain control, because it allows quick mobilization, intense respiratory physiotherapy and reduces postoperative morbidity. Unfortunately, patients under thoracotomy, incur a significant risk of chronic pain. Although there are guidelines for the management of post-operative pain relief in these patients, however there is no widespread surgical or anesthetic "gold standard." In the present article it has been investigated the current literature related to the proposed therapies and other interventions that were recommended for post-operative pain relief after thoracotomy. The treatment of chronic pain after thoracotomy is difficult and includes physical rehabilitation techniques and multimodal approach. More and more researchers support that minimization of acute post-operative pain is the best method so as to avoid, prevent or reduce post- thoracotomy pain syndrome.